2012
DOI: 10.1557/jmr.2012.309
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DNA-encapsulated silica elaborated by sol–gel routes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Several cold and dry storage strategies, eventually combined and improved by storage additives, , are used to store/transport DNA. Alternative solutions, such as DNA encapsulation into porous silica matrix , or within layered metal hydroxide, , have also been proposed.…”
mentioning
confidence: 99%
“…Several cold and dry storage strategies, eventually combined and improved by storage additives, , are used to store/transport DNA. Alternative solutions, such as DNA encapsulation into porous silica matrix , or within layered metal hydroxide, , have also been proposed.…”
mentioning
confidence: 99%
“…32 In a previous study, EtBr molecules were shown to intercalate into ds-DNA molecules encapsulated in an amorphous silica network. 26 So, accumulation of EtBr onto E-silica DNA , as evidenced by optical analyses, indicates presence of preferential sites for EtBr accommodation in DNA even after encapsulation state. Hence, the native base-paired, helix conformation of DNA seems to be preserved in the gel after sol-gel transformation.…”
Section: Resultsmentioning
confidence: 93%
“…As EtBr is a planar molecule and can intercalate only into ds-DNA, it was used as a marker to show that ds-DNA molecules were trapped in silica and the procedure was described elsewhere. 26 Basically in a typical test, an EtBr solution was prepared by dissolving EtBr powders in DI-water (10 µg/mL). Then, E-silica DNA and E-silica dAMP gel powders (35 mg) were immersed into EtBr solution (3.5 mL) for 3 h. After 3 h, the powders were separated from the solution by centrifugation (10,000 r/min, 5 min) and the supernatants were analyzed by UV-Vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the TMG precursor might favor the dissociation reaction more than TMI. Finally, the distorted peak positioned between −85 and −120 ppm is clearly assignable to silanol groups and bridged silicon of Q 3+4 (O 3 -Si-OH, O 4 -Si) [100,102].…”
Section: Determination Of Ligand Implementationmentioning
confidence: 99%